Governance and Food Insecurity in Nigeria: The Nexus - Ibrahim, Bashir; Ya’u, Muhammad-Sani (Kashere Journal of Politics and International Relations, 2025)
The Nigeria’s persistent food insecurity paradox despite its vast agricultural potentials, underscores the debilitating effects of bad governance. This study employs the theory of primitive capitalist accumulation to examine the relationship between governance failures and food insecurity in Nigeria. Relying on secondary data from reputable sources, including academic journals, reports from international organizations, and government documents, this research reveals how Nigeria’s governance landscape perpetuates food insecurity. The analysis highlights how primitive accumulation manifested through land grabbing, displacement of smallholder farmers, and exploitation of agricultural resources, exacerbates food insecurity. Furthermore, the study identifies corruption, patronage politics, and weak institutional frameworks as key governance failures undermining Nigeria’s food security. The findings suggest that addressing food insecurity in Nigeria requires transformative governance reforms that prioritize the interests of smallholder farmers, promote equitable land distribution, and ensure transparency and accountability in agricultural policies.